Amyloid precursor proteins are protective in Drosophila models of progressive neurodegeneration - Wentzell, Jill S. (2012)
The processing of Amyloid Precursor Proteins (APPs) results in several fragments, including soluble N-terminal ectodomains (sAPPs) and C-terminal intracellular domains (AICD). sAPPs have been ascribed neurotrophic or neuroprotective functions in cell culture, although β-cleaved sAPPs can have deleterious effects and trigger neuronal cell death. Here we describe a neuroproprotective function of APP and fly APPL (Amyloid Precursor Protein-like) in vivo in several Drosophila mutants with progressive neurodegeneration. We show that expression of the N-terminal ectodomain is sufficient to suppress the progressive degeneration in these mutants and that the secretion of the ectodomain is required for this function. In addition, a protective effect is achieved by expressing kuzbanian (which has α-secretase activity) whereas expression of fly and human BACE aggravates the phenotypes, suggesting that the protective function is specifically mediated by the α-cleaved ectodomain. Furthermore, genetic and molecular studies suggest that the N-terminal fragments interact with full-length APPL activating a downstream signaling pathway via the AICD. Because we show protective effects in mutants that affect different genes (AMP-activated protein kinase, MAP1b, rasGAP), we propose that the protective effect is not due to a genetic interaction between APPL and these genes but a more general aspect of APP proteins. The result that APP proteins and specifically their soluble α-cleaved ectodomains can protect against progressive neurodegeneration in vivo provides support for the hypothesis that a disruption of the physiological function of APP could play a role in the pathogenesis of Alzheimer’s Disease.